Evolution and extensive reassortment of H5 influenza viruses isolated from wild birds in China over the past decade. Issue 1 (1st January 2020) - Cui, Yanfang; Li, Yulei; Li, Minghui; Zhao, Lu; Wang, Deli; Tian, Jingman; Bai, Xiaoli; Ci, Yanpeng; Wu, Shanshan; Wang, Fei; Chen, Xiaomei; Ma, Shujie; et al.
ABSTRACT: Lethal infection of wild birds with different subtypes of H5 viruses continuously occur. To investigate the genetic evolution and pathogenicity of H5 viruses in wild birds, we performed a detailed genetic and biologic analysis of 27 viruses, including H5N1, H5N2, H5N6, and H5N8 subtypes, that were responsible for avian influenza outbreaks in wild birds in China over the past decade. We found that these 27 viruses, bearing different clades/subclades of HA, were complicated reassortants and formed 12 different genotypes. Ten of the viruses tested were highly pathogenic in chickens, but showed distinct pathotypes in ducks and mice. Five of these 10 viruses, which were all from clade2.3.4.4, could bind human-type receptors. Our findings reveal the diversity of the genetic and biologic properties of H5 viruses circulating in wild birds and highlight the need to carefully monitor and evaluate the risks these viruses pose to animal and public health.